2017
DOI: 10.1038/s41598-017-06789-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-hypoxia Invasion of the fetal brain by multidrug resistant Staphylococcus

Abstract: Herein we describe an association between activation of inflammatory pathways following transient hypoxia and the appearance of the multidrug resistant bacteria Staphylococcus simulans in the fetal brain. Reduction of maternal arterial oxygen tension by 50% over 30 min resulted in a subseiuent significant over-expression of genes associated with immune responses 24 h later in the fetal brain. The activated genes were consistent with stimulation by bacterial lipopolysaccharide; an influx of macrophages and appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 38 publications
4
42
2
Order By: Relevance
“…); recently, we have linked these responses to the appearance of bacterial strains in the cerebral cortex and placenta (Zarate et al . ). In the present study, interestingly, we also detected bacterial 16S expression in the fetal brain in all four groups (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…); recently, we have linked these responses to the appearance of bacterial strains in the cerebral cortex and placenta (Zarate et al . ). In the present study, interestingly, we also detected bacterial 16S expression in the fetal brain in all four groups (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…During HH, maternal cortisol levels rises substantially (Chang & Wood, ) and, once released, we speculate that it might have a particular effect on the placental circulation leading to the release of bacteria previously harbored in the fetal membranes (Zarate et al . ). These microorganisms could be the potential factor for the inflammation response observed in fetal brain tissues and kidneys (Chang et al .…”
Section: Discussionmentioning
confidence: 97%
“…Using pregnant ewes, Zarate and colleagues recently demonstrated that maternal and/or fetal hypoxic stress later in pregnancy upregulates neuro-immune pathways associated with LPS stimulation 65 . Under these conditions, this group detected live antibiotic-resistant Staphylococcus simulans in the placenta and fetal brain, suggesting that specific physiological changes associated with hypoxic stress, such as increased blood flow and barrier permeability, can promote the passage of maternal bacteria across the placenta and fetal blood-brain barrier 65 . Similarly, maternal stress levels or other unknown physiological changes during pregnancy may explain the presence of R. insidiosa in the human placenta.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was recently shown that hypoxia promotes bacterial entry to the brain, suggesting synergy between different insults that should be considered in future studies (Zarate et al . ).…”
Section: Central Nervous System Barriersmentioning
confidence: 97%